Engineering a nifurtimox nanosuspension: toward improved pharmaceutical attributes - María Sol Magi; Lucía Lopez-Vidal; Mónica Cristina García; Santiago Daniel Palma; Alvaro Federico Jimenez-Kairuz (Drug Delivery and Translational Research, 2026)

Tracing ancient climates: the role of the weathering mantle in the Río de la Plata Craton's history - Camila Ferreyra; Lucía E. Gómez-Peral; M. Julia Arrouy; Victoria Penzo; M. Sol Raigemborn; Daniel G. Poiré (International Journal of Earth Sciences, 2026)

Doppler ultrasound assessment of uterine artery in canine endometritis - Sol Arioni; Marlene Huk; Pablo R. Batista; Daniel O. Arias; Cristina Gobello; Paula G. Blanco (Theriogenology, 2025)

Maastrichtian climate of southern Patagonia (Argentina): An approach from paleosols of the dinosaur-bearing Chorrillo Formation - M. Sol Raigemborn; Sabrina Lizzoli; Damián Moyano-Paz; Augusto N. Varela; Daniel G. Poiré; Valeria S. Perez Loinaze; Ezequiel I. Vera; Makoto Manabe; Takanobu Tsuihiji; Takashi Sano; Fernando E. Novas (Cretaceous Research, 2025)

Assessing genetics, biophysical, and management factors related to soybean seed protein variation in Brazil - María Sol Zelaya Arce; Eduardo Lago Lago Tagliapietra; José Eduardo Minussi Winck; Alexandre Ferigolo Alves; Felipe Schmidt Dalla Porta; Tiago Broilo Facco; Nereu Augusto Streck; Mauricio Fornalski Soares; Gregori Da Encarnação Ferrão; Daniel Debona; Claudio Hideo Martins da Costa; Rodrigo Merighi Bega; et al. (European Journal of Agronomy, 2025)

Loss of species and functions in a deforested megadiverse tropical forest - Lisieux Fuzessy; Sandrine Pavoine; Laura Cardador; Joan Maspons; Daniel Sol (Conservation Biology, 2024)
Tropical species richness is threatened by habitat degradation associated with land‐use conversion, yet the consequences for functional diversity remain little understood. Progress has been hindered by difficulties in obtaining comprehensive species‐level trait information to characterize entire assemblages and insufficient appreciation that increasing land‐cover heterogeneity potentially compensates for species loss. We examined the impacts of tropical deforestation associated with land‐use heterogeneity on bird species richness, functional redundancy, functional diversity, and associated components (i.e., alpha diversity, species dissimilarity, and interaction strength of the relationship between abundance and functional dissimilarity). We analyzed over 200 georeferenced bird assemblages in the Atlantic Forest of Brazil. We characterized the functional role of the species of each assemblage and modeled biodiversity metrics as a function of forest cover and land‐cover heterogeneity. Replacement of native Atlantic Forest with a mosaic of land uses (e.g., agriculture, pastures, and urbanization) reduced bird species richness in a nonrandom way. Core forest species, or species considered sensitive to edges, tended to be absent in communities in heterogenous environments. Overall, functional diversity and functional redundancy of bird species were not affected by forest loss. However, birds in highly heterogenous habitats were functionally distinct from birds in forest, suggesting a shift in community composition toward mosaic‐exclusive species led by land‐cover heterogeneity. Threatened species of the Atlantic Forest did not seem to tolerate degraded and heterogeneous environments; they remained primarily in areas with large forest tracts. Our results shed light on the complex effects of native forest transformation to mosaics of anthropogenic landscapes and emphasize the importance of considering the effects of deforestation and land‐use heterogeneity when assessing deforestation effects on Neotropical biodiversity.

Toward a unified framework for studying behavioural tolerance - Catherine Čapkun-Huot; Daniel T. Blumstein; Dany Garant; Daniel Sol; Denis Réale (Trends in Ecology & Evolution, 2024)

Interrelation between extracellular polymer substances (EPSs) and MPs in an MBR - Carla González-Menéndez; Daniel Sol; Amanda Laca; Adriana Laca; Mario Díaz (Journal of Environmental Chemical Engineering, 2024)

Organ-specific volatiles from Sonoran desert Krameria flowers as potential signals for oil-collecting bees - Maria Sol Balbuena; Stephen L. Buchmann; Daniel R. Papaj; Robert A. Raguso (Phytochemistry, 2024)

A standard analytical approach and establishing criteria for microplastic concentrations in wastewater, drinking water and tap water - Daniel Sol; Carmen Solís-Balbín; Amanda Laca; Adriana Laca; Mario Díaz (Science of The Total Environment, 2023)

Two karst events bounding drastic changes in the Neoproterozoic Tandilia Basin history, Argentina: paleogeographic relevance - Lucía E. Gómez-Peral; M. Julia Arrouy; M. Sol Raigemborn; Camila Ferreyra; Victoria Penzo; Alcides N. Sial; Daniel G. Poiré (International Journal of Earth Sciences, 2023)

Microplastics in Sewage Sludge: A review - Claudio Casella; Daniel Sol; Adriana Laca; Mario Díaz (Environmental Science and Pollution Research, 2023)

Destruction and entrainment of microplastics in ozonation and wet oxidation processes - Carmen Solís-Balbín; Daniel Sol; Amanda Laca; Adriana Laca; Mario Díaz (Journal of Water Process Engineering, 2023)

Contribution of household dishwashing to microplastic pollution - Daniel Sol; Andrea Menéndez-Manjón; Sofía Carrasco; Jacinto Crisóstomo-Miranda; Amanda Laca; Adriana Laca; Mario Díaz (Environmental Science and Pollution Research, 2023)
At household level, clothes washing has been recognised as an emitter of microplastics (MPs) into the environment and it is supposed that dishwashing is also a source of MPs, although little attention has been paid so far. In this work, the emission of MPs released from dishwashing procedures at household level has been studied. The effect of different parameters such as time, temperature and type of detergent has been analysed. In addition, the MP content of tap water has been evaluated in order to determine its contribution to the MPs in dishwasher effluent. Results showed that when the dishwasher was operated empty with a pre-wash programme (15 min and room water temperature), between 207 and 427 MPs were released per load (3 L), whereas this value increased notably with an intensive programme (164 min and water at 70 °C) (1025–1370 MPs per load, 15 L), which highlighted the effect of temperature and time on MP release. Additionally, when a polypropylene lunch box was washed, the number of MPs released increased by 14 ± 3 MPs and 166 ± 12 MPs of total. Finally, the influence of the use of detergent with the dishwasher empty and containing lunch boxes has been studied. With detergent, 35–54% more MPs were released from dishwasher accessories, whereas no additional release took place from lunch boxes. This work shows for the first time the important contribution of domestic dishwashing to MP pollution and the environmental benefits of using more environmentally friendly materials in both dishwashing machine accessories and food utensils.

Selective brain regional changes in lipid profile with human aging - Natalia Mota-Martorell; Pol Andrés-Benito; Meritxell Martín-Gari; José Daniel Galo-Licona; Joaquim Sol; Anna Fernández-Bernal; Manuel Portero-Otín; Isidro Ferrer; Mariona Jove; Reinald Pamplona (GeroScience, 2022)
Fatty acids are key components in the structural diversity of lipids and play a strategic role in the functional properties of lipids which determine the integrity of neuronal and glial cell membranes, the generation of lipid signaling mediators, and the chemical reactivity of acyl chains. The present study analyzes using gas chromatography the fatty acid profiles of 13 regions of the human central nervous system in healthy individuals ranging from 40 to 80 years old. The outcomes suggest the existence of general traits in fatty acid composition such as an average chain length of 18 carbon atoms, high monounsaturated fatty acid content, and predominance in polyunsaturated fatty acids of those of series n-6 over series n-3 which are shared by all brain regions regardless of age. Our results also show a general sustained and relatively well-preserved lipid profile throughout the adult lifespan in most studied regions (olive, upper vermis, substantia nigra, thalamus, hippocampus, putamen, caudate, occipital cortex, parietal cortex, entorhinal cortex, and frontal cortex) with minor changes that are region-dependent. In contrast, of particular relevance is the involvement of the inferior temporal cortex and cingulate cortex. It is proposed that during normal human brain aging, the lipid profile is resistant to changes with age in most human brain regions to ensure cell survival and function, but some particular regions involved in specific memory domains are greatly affected.

A test of Darwin’s naturalization conundrum in birds reveals enhanced invasion success in the presence of close relatives - Daniel Sol; Joan Garcia‐Porta; Cesar González‐Lagos; Alex L. Pigot; Christopher Trisos; Joseph A. Tobias (Ecology Letters, 2022)
Biological invasions pose one of the most severe environmental challenges of the twenty‐first century. A longstanding idea is that invasion risk is predictable based on the phylogenetic distance – and hence ecological resemblance – between non‐native and native species. However, current evidence is contradictory. To explain these mixed results, it has been proposed that the effect is scale‐dependent, with invasion inhibited by phylogenetic similarity at small spatial scales but enhanced at larger scales. Analyzing invasion outcomes in a global sample of bird communities, we find no evidence to support this hypothesis. Instead, our results suggest that invaders are locally more successful in the presence of closely related and ecologically similar species, at least in human‐altered environments where the majority of invasions have occurred. Functional trait analyses further confirm that the ecological niches of invaders are phylogenetically conserved, supporting the notion that successful invasion in the presence of close relatives is driven by shared adaptations to the types of niches available in novel environments.

Contrasting Impacts of Cultivated Exotics on the Functional Diversity of Domestic Gardens in Three Regions with Different Aridity - Josep Padullés Cubino; Dorothy Borowy; Sonja Knapp; Zdeňka Lososová; Carlo Ricotta; Stefan Siebert; Jeannine Cavender-Bares; Daniel Sol; Alienor Jeliazkov; Christopher Swan (Ecosystems, 2021)
Cultivated exotic plants are often introduced for their aesthetic value and today comprise a substantial fraction of the flora of urban domestic gardens. Yet, their relative contribution to the functional diversity of domestic gardens and how it changes across different climate zones is insufficiently understood. Here, we investigated whether the effects of cultivated exotics on functional diversity of three plant traits related to plant aesthetics (that is, plant showiness, plant height, and leaf area) varied in suburban domestic gardens in three regions (Minnesota, USA; Alt Empordà, Spain; and central South Africa) that differ in aridity. For each garden, we calculated the mean and variance of each plant trait considering all co-occurring species and also splitting them into co-occurring cultivated exotics and natives. Our results revealed that mean plant showiness increased linearly with the proportion of cultivated exotics both across and within studied regions. Moreover, co-occurring cultivated exotics were, on average, showier than natives in all regions, but differences in their trait variances were context-dependent. The interaction between cultivated exotics and aridity explained variation in mean plant height and leaf area better than either predictor alone, with the effect of cultivated exotics being stronger in more arid regions. Accordingly, co-occurring cultivated exotics were taller and had larger leaves than natives in warmer and drier regions, while the opposite was true in cooler and wetter regions. Our study highlights the need to consider the combined effects of exotic species and climate in future studies of urban ecology.

The worldwide impact of urbanisation on avian functional diversity - Daniel Sol; Christopher Trisos; Cesc Múrria; Alienor Jeliazkov; Cesar González‐Lagos; Alex L. Pigot; Carlo Ricotta; Christopher M. Swan; Joseph A. Tobias; Sandrine Pavoine (Ecology Letters, 2020)
Urbanisation is driving rapid declines in species richness and abundance worldwide, but the general implications for ecosystem function and services remain poorly understood. Here, we integrate global data on bird communities with comprehensive information on traits associated with ecological processes to show that assemblages in highly urbanised environments have substantially different functional composition and 20% less functional diversity on average than surrounding natural habitats. These changes occur without significant decreases in functional dissimilarity between species; instead, they are caused by a decrease in species richness and abundance evenness, leading to declines in functional redundancy. The reconfiguration and decline of native functional diversity in cities are not compensated by the presence of exotic species but are less severe under moderate levels of urbanisation. Thus, urbanisation has substantial negative impacts on functional diversity, potentially resulting in impaired provision of ecosystem services, but these impacts can be reduced by less intensive urbanisation practices.

Fast attrition of springtail communities by experimental drought and richness–decomposition relationships across Europe - Guille Peguero; Daniel Sol; Miquel Arnedo; Henning Petersen; Sandrine Salmon; Jean‐François Ponge; Joan Maspons; Bridget Emmett; Claus Beier; Inger K. Schmidt; Albert Tietema; Paolo De Angelis; et al. (Global Change Biology, 2019)
Soil fauna play a fundamental role on key ecosystem functions like organic matter decomposition, although how local assemblages are responding to climate change and whether these changes may have consequences to ecosystem functioning is less clear. Previous studies have revealed that a continued environmental stress may result in poorer communities by filtering out the most sensitive species. However, these experiments have rarely been applied to climate change factors combining multiyear and multisite standardized field treatments across climatically contrasting regions, which has limited drawing general conclusions. Moreover, other facets of biodiversity, such as functional and phylogenetic diversity, potentially more closely linked to ecosystem functioning, have been largely neglected. Here, we report that the abundance, species richness, phylogenetic diversity, and functional richness of springtails (Subclass Collembola), a major group of fungivores and detritivores, decreased within 4 years of experimental drought across six European shrublands. The loss of phylogenetic and functional richness was higher than expected by the loss of species richness, leading to communities of phylogenetically similar species sharing evolutionary conserved traits. Additionally, despite the great climatic differences among study sites, we found that taxonomic, phylogenetic, and functional richness of springtail communities alone were able to explain up to 30% of the variation in annual decomposition rates. Altogether, our results suggest that the forecasted reductions in precipitation associated with climate change may erode springtail communities and likely other drought‐sensitive soil invertebrates, thereby retarding litter decomposition and nutrient cycling in ecosystems.

Countryside Biogeography: the Controls of Species Distributions in Human-Dominated Landscapes - Luke Owen Frishkoff; Alison Ke; Inês Santos Martins; Elissa M. Olimpi; Daniel Sol Karp (Current Landscape Ecology Reports, 2019)

Risk-taking behavior, urbanization and the pace of life in birds - Daniel Sol; Joan Maspons; Alejandro Gonzalez-Voyer; Ignacio Morales-Castilla; László Zsolt Garamszegi; Anders Pape Møller (Behavioral Ecology and Sociobiology, 2018)

Tropical insect diversity: evidence of greater host specialization in seed‐feeding weevils - Guille Peguero; Raúl Bonal; Daniel Sol; Alberto Muñoz; Victoria L. Sork; Josep M. Espelta (Ecology, 2017)
Host specialization has long been hypothesized to explain the extraordinary diversity of phytophagous insects in the tropics. However, addressing this hypothesis has proved challenging because of the risk of over‐looking rare interactions, and hence biasing specialization estimations, and the difficulties to separate the diversity component attributable to insect specialization from that related to host diversity. As a result, the host specialization hypothesis lacks empirical support for important phytophagous insect clades. Here, we test the hypothesis in a radiation of seed‐feeding insects, acorn weevils ( Curculio spp.), sampled in temperate and tropical regions (California and Nicaragua, respectively) with an equivalent pool of oak host species. Using DNA sequences from three low‐copy genes, we delimited to species level 778 weevil larvae extracted from host seeds and assessed their phylogenetic relationships by Maximum Likelihood and Bayesian inference. We then reconstructed the oak‐weevil food webs and examined differences in alpha, beta and gamma diversity using Hill numbers of effective species. We found a higher alpha, beta and gamma diversity of weevils in Nicaragua compared to California despite similar richness of host species at both local and regional level. By means of Bayesian mixed models, we also found that tropical weevil species were highly specialized both in terms of host range and interaction strength, whereas their temperate congeners had a broader taxonomic and phylogenetic host spectrum. Finally, in Nicaraguan species, larval body size was highly correlated with the size of the acorns infested, as would be expected by a greater host specialization, whereas in California this relationship was absent. Altogether, these lines of evidence support the host specialization hypothesis and suggest contrasting eco‐evolutionary dynamics in tropical and temperate regions even in absence of differences in host diversity.

Urbanisation and the loss of phylogenetic diversity in birds - Daniel Sol; Ignasi Bartomeus; César González‐Lagos; Sandrine Pavoine (Ecology Letters, 2017)
Despite the recognised conservation value of phylogenetic diversity, little is known about how it is affected by the urbanisation process. Combining a complete avian phylogeny with surveys along urbanisation gradients from five continents, we show that highly urbanised environments supported on average 450 million fewer years of evolutionary history than the surrounding natural environments. This loss was primarily caused by species loss and could have been higher had not been partially compensated by the addition of urban exploiters and some exotic species. Highly urbanised environments also supported fewer evolutionary distinctive species, implying a disproportionate loss of evolutionary history. Compared with highly urbanised environments, changes in phylogenetic richness and evolutionary distinctiveness were less substantial in moderately urbanised environments. Protecting pristine environments is therefore essential for maintaining phylogenetic diversity, but moderate levels of urbanisation still preserve much of the original diversity.

Competition, niche opportunities and the successful invasion of natural habitats - Miquel Vall-llosera; Francesc Llimona; Miquel de Cáceres; Sergi Sales; Daniel Sol (Biological Invasions, 2016)

Random processes and phylogenetic loss caused by plant invasions - Oriol Lapiedra; Daniel Sol; Anna Traveset; Montserrat Vilà (Global Ecology and Biogeography, 2015)
Aim Although biological invasions represent a major cause of biodiversity loss, the actual mechanisms driving species extinctions remain insufficiently understood. Here we investigate the role of three processes as drivers of phylogenetic loss in invaded local plant communities, namely the ‘biotic resistance’, ‘environmental filtering’ and ‘functional equivalence’ hypotheses. Location B alearic I slands (western M editerranean). Methods We quantified the phylogenetic diversity and structure of 109 pairs of invaded and non‐invaded local plant communities from two M editerranean islands. Each pair contained one control plot and one plot invaded either by the deciduous tree A ilanthus altissima , the succulent subshrubs C arpobrotus spp. or the pseudoannual geophyte O xalis pes‐caprae . We combined generalized linear models, analyses of phylogenetic community structure and generalized linear mixed models using a M arkov chain M onte C arlo technique ( MCMCglmm ) to contrast the ‘biotic resistance’, ‘environmental filtering’ and ‘functional equivalence’ hypotheses. Results While the phylogenetic structure of the non‐invaded communities was not more clustered or overdispersed than expected by chance, minimum phylogenetic distance to the invasive species increased in invaded assemblages, in which the magnitude of phylogenetic diversity loss ranged from 6 to 37% depending on the invader's identity. Invader or island identity did not explain the probabilities of native species becoming locally extinct. Rather, the likelihood of extinction was mainly explained by species abundance, with scarcer species exhibiting a higher chance of becoming locally extinct. Species identity explained a small fraction of the variation in extinction risk (12%), independently of each species' evolutionary history. Main conclusions The most relevant driver of local extinction is a stochastic process where less abundant species tend to disappear more frequently irrespective of their evolutionary history. This has strong implications for conservation because it suggests that in the study region the invaders are unlikely to drive regional and global extinctions except in cases where the native species is already rare.

Urbanisation tolerance and the loss of avian diversity - Daniel Sol; Cesar González‐Lagos; Darío Moreira; Joan Maspons; Oriol Lapiedra (Ecology Letters, 2014)
Urbanisation is considered an important driver of current biodiversity loss, but the underlying causes are not fully understood. It is generally assumed that this loss reflects the fact that most organisms do not tolerate well the environmental alterations associated with urbanisation. Nevertheless, current evidence is inconclusive and the alternative that the biodiversity loss is the result of random mechanisms has never been evaluated. Analysing changes in abundance between urbanised environments and their non‐urbanised surroundings of > 800 avian species from five continents, we show here that although random processes account for part of the species loss associated with urbanisation, much of the loss is associated with a lack of appropriate adaptations of most species for exploiting resources and avoiding risks of the urban environments. These findings have important conservation implications because the extinction of species with particular features should have higher impact on biodiversity and ecosystem function than a random loss.

Addressing a critique of the TEASI framework for invasive species risk assessment - Brian Leung; Nuria Roura‐Pascual; Sven Bacher; Jaakko Heikkilä; Lluis Brotons; Mark A Burgman; Katharina Dehnen‐Schmutz; Franz Essl; Philip E Hulme; David M Richardson; Daniel Sol; Montserrat Vilà (Ecology Letters, 2013)
We address criticism that the Transport, Establishment, Abundance, Spread, Impact (TEASI) framework does not facilitate objective mapping of risk assessment methods nor defines best practice. We explain why TEASI is appropriate for mapping, despite inherent challenges, and how TEASI offers considerations for best practices, rather than suggesting one best practice.

TEASIng apart alien species risk assessments: a framework for best practices - Brian Leung; Nuria Roura‐Pascual; Sven Bacher; Jaakko Heikkilä; Lluis Brotons; Mark A. Burgman; Katharina Dehnen‐Schmutz; Franz Essl; Philip E. Hulme; David M. Richardson; Daniel Sol; Montserrat Vilà (Ecology Letters, 2012)
Some alien species cause substantial impacts, yet most are innocuous. Given limited resources, forecasting risks from alien species will help prioritise management. Given that risk assessment ( RA ) approaches vary widely, a synthesis is timely to highlight best practices. We reviewed quantitative and scoring RA s, integrating > 300 publications into arguably the most rigorous quantitative RA framework currently existing, and mapping each study onto our framework, which combines Transport, Establishment, Abundance, Spread and Impact ( TEASI ). Quantitative models generally measured single risk components (78% of studies), often focusing on Establishment alone (79%). Although dominant in academia, quantitative RA s are underused in policy, and should be made more accessible. Accommodating heterogeneous limited data, combining across risk components, and developing generalised RA s across species, space and time without requiring new models for each species may increase attractiveness for policy applications. Comparatively, scoring approaches covered more risk components (50% examined > 3 components), with Impact being the most common component (87%), and have been widely applied in policy (> 57%), but primarily employed expert opinion. Our framework provides guidance for questions asked, combining scores and other improvements. Our risk framework need not be completely parameterised to be informative, but instead identifies opportunities for improvement in alien species RA .

The paradox of invasion in birds: competitive superiority or ecological opportunism? - Daniel Sol; Ignasi Bartomeus; Andrea S. Griffin (Oecologia, 2012)

Deconstructing the native–exotic richness relationship in plants - Ignasi Bartomeus; Daniel Sol; Joan Pino; Paloma Vicente; Xavier Font (Global Ecology and Biogeography, 2012)
Aim Classic theory suggests that species‐rich communities should be more resistant to the establishment of exotic species than species‐poor communities. Although this theory predicts that exotic species should be less diverse in regions that contain more native species, macroecological analyses often find that the correlation between exotic and native species richness is positive rather than negative. To reconcile results with theory, we explore to what extent climatic conditions, landscape heterogeneity and anthropogenic disturbance may explain the positive relationship between native and exotic plant richness. Location Catalonia (western Mediterranean region). Methods We integrated floristic records and GIS‐based environmental measures to make spatially explicit 10‐km grid cells. We asked whether the observed positive relationship between native and exotic plant richness ( R 2 = 0.11) resulted from the addition of several negative correlations corresponding to different environmental conditions identified with cluster analysis. Moreover, we directly quantified the importance of common causal effects with a structural equation modelling framework. Results We found no evidence that the relationship between native and exotic plant richness was negative when the comparison was made within environmentally homogeneous groups. Although there were common factors explaining both native and exotic richness, mainly associated with landscape heterogeneity and human pressure, these factors only explained 17.2% of the total correlation. Nevertheless, when the comparison was restricted to native plants associated with human‐disturbed (i.e. ruderal) ecosystems, the relationship was stronger ( R 2 = 0.52) and the fraction explained by common factors increased substantially (58.3%). Main conclusions While our results confirm that the positive correlation between exotic and native plant richness is in part explained by common extrinsic factors, they also highlight the great importance of anthropic factors that – by reducing biotic resistance – facilitate the establishment and spread of both exotic and native plants that tolerate disturbed environments.

Polycyclic Aromatic Hydrocarbons and Risk to Threatened and Endangered Chinook Salmon in the Lower Columbia River Estuary - Gladys K. Yanagida; Bernadita F. Anulacion; Jennie L. Bolton; Daryle Boyd; Daniel P. Lomax; O. Paul Olson; Sean Y. Sol; Maryjean Willis; Gina M. Ylitalo; Lyndal L. Johnson (Archives of Environmental Contamination and Toxicology, 2012)

Total Iron, Heme Iron, Zinc, and Copper Content in Rabbit Meat and Viscera - Carolina Valenzuela; Daniel Lopez de Romaña; Camila Schmiede; María Sol Morales; Manuel Olivares; Fernando Pizarro (Biological Trace Element Research, 2011)

Total Iron and Heme Iron Content and their Distribution in Beef Meat and Viscera - Carolina Valenzuela; Daniel López de Romaña; Manuel Olivares; María Sol Morales; Fernando Pizarro (Biological Trace Element Research, 2009)

The comparative analysis of historical alien introductions - Daniel Sol; Montserrat Vilà; Ingolf Kühn (Biological Invasions, 2008)

Random sampling, abundance–extinction dynamics and niche‐filtering immigration constraints explain the generation of species richness gradients - Jofre Carnicer; Lluís Brotons; Daniel Sol; Miquel De Cáceres (Global Ecology and Biogeography, 2008)
Aim The paradigm that species’ patterns of distribution, abundance and coexistence are the result of adaptations of the species to their niches has recently been challenged by evidence that similar patterns may be generated by simple random processes. We argue here that a better understanding of macroecological patterns requires an integration of both ecological and neutral stochastic approaches. We demonstrate the utility of such an integrative approach by testing the sampling hypothesis in a species–energy relationship of forest bird species. Location A Mediterranean biome in Catalonia, Spain. Methods To test the sampling hypothesis we designed a metacommunity model that reproduces the stochastic sampling from a regional pool to predict local species richness variation. Four conceptually different sampling procedures were evaluated. Results We showed that stochastic sampling processes predicted a substantial part (over 40%) of the observed variation in species richness, but left considerable variation unexplained. This remaining variation in species richness may be better understood as the result of alternative ecological processes. First, the sampling model explained more variation in species richness when the probability that a species colonises a new locality was assumed to increase with its niche width, suggesting that ecological differences between species matter when it comes to explaining macroecological patterns. Second, extinction risk was significantly lower for species inhabiting high‐energy regions, suggesting that abundance–extinction processes play a significant role in shaping species richness patterns. Main conclusions We conclude that species–energy relationships may not simply be understood as a result of either ecological or random sampling processes, but more likely as a combination of both.

Community‐based processes behind species richness gradients: contrasting abundance–extinction dynamics and sampling effects in areas of low and high productivity - Jofre Carnicer; Lluís Brotons; Daniel Sol; Pedro Jordano (Global Ecology and Biogeography, 2007)
Aim To consider the role of local colonization and extinction rates in explaining the generation and maintenance of species richness gradients at the regional scale. Location A Mediterranean biome (oak forests, deciduous forests, shrublands, pinewoods, firwoods, alpine heathlands, crops) in Catalonia, Spain. Methods We analysed the relative importance of direct and indirect effects of community size in explaining species richness gradients. Direct sampling effects of community size on species richness are predicted by Hubbell's neutral theory of biodiversity and biogeography. The greater the number of individuals in a locality, the greater the number of species expected by random direct sampling effects. Indirect effects are predicted by the abundance–extinction hypothesis, which states that in more productive sites increased population densities and reduced extinction rates may lead to high species richness. The study system was an altitudinal gradient of forest bird species richness. Results We found significant support for the existence of both direct and indirect effects of community size in species richness. Thus, both the neutral and the abundance–extinction hypotheses were supported for the altitudinal species richness gradient of forest birds in Catalonia. However, these mechanisms seem to drive variation in species richness only in low‐productivity areas; in high‐productivity areas, species richness was uncorrelated with community size and productivity measures. Main conclusions Our results support the existence of a geographical mosaic of community‐based processes behind species richness gradients, with contrasting abundance–extinction dynamics and sampling effects in areas of low and high productivity.

DOES DIVING LIMIT BRAIN SIZE IN CETACEANS? - Lori Marino; Daniel Sol; Kristen Toren; Louis Lefebvre (Marine Mammal Science, 2006)
We test the longstanding hypothesis, known as the dive constraint hypothesis, that the oxygenation demands of diving pose a constraint on aquatic mammal brain size.Using a sample of 23 cetacean species we examine the relationship among six different measures of relative brain size, body size, and maximum diving duration. Unlike previous tests we include body size as a covariate and perform independent contrast analyses to control for phylogeny. We show that diving does not limit brain size in cetaceans and therefore provide no support for the dive constraint hypothesis. Instead, body size is the main predictor of maximum diving duration in cetaceans. Furthermore, our findings show that it is important to conduct robust tests of evolutionary hypotheses by employing a variety of measures of the dependent variable, in this case, relative brain size.

Establishment Success across Convergent Mediterranean Ecosystems: an Analysis of Bird Introductions - SALIT KARK; DANIEL SOL (Conservation Biology, 2005)
Concern over the impact of invaders on biodiversity and on the functioning of ecosystems has generated a rising tide of comparative analyses aiming to unveil the factors that shape the success of introduced species across different regions. One limitation of these studies is that they often compare geographically rather than ecologically defined regions. We propose an approach that can help address this limitation: comparison of invasions across convergent ecosystems that share similar climates. We compared avian invasions in five convergent mediterranean climate systems around the globe. Based on a database of 180 introductions representing 121 avian species, we found that the proportion of bird species successfully established was high in all mediterranean systems (more than 40% for all five regions). Species differed in their likelihood to become established, although success was not higher for those originating from mediterranean systems than for those from nonmediterranean regions. Controlling for this taxonomic effect with generalized linear mixed models, species introduced into mediterranean islands did not show higher establishment success than those introduced to the mainland. Susceptibility to avian invaders, however, differed substantially among the different mediterranean regions. The probability that a species will become established was highest in the Mediterranean Basin and lowest in mediterranean Australia and the South African Cape. Our results suggest that many of the birds recently introduced into mediterranean systems, and especially into the Mediterranean Basin, have a high potential to establish self‐sustaining populations. This finding has important implications for conservation in these biologically diverse hotspots.

Parasite mediated mortality and host immune response explain age-related differences in blood parasitism in birds - Daniel Sol; Roger Jovani; Jordi Torres (Oecologia, 2003)